Perancangan User Interface Aplikasi Travelingyuk Berbasis Mobile Menggunakan Metode Human Centered Design (HCD) - Shandya Fajar Widyono; Niken Hendrakusma; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
According to Kominfo, smartphones are the most widely used user with around 50.08% of users compared to computers or laptops. The high flexibility makes mobile devices more commonly used by people. PT. Traveling Media Network (Travelingyuk) is a company that specializes in travel agency. Until now, Travelingyuk still has not had a mobile media for their information of tourism. To enhance the competitiveness of Travelingyuk to other travel agency companies, therefore, a mobile-based application is needed. A good application is the one that the users can accept and use easily and unambiguously. To achieve the goal, Travelingyuk needs a user-based interface design in the mobile application. The right method to create a user-based design is Human Centered Design (HCD), because this method makes the users (humans) the center for determining the design. This research discusses how to create user interfaces of the mobile-based application used by Travelingyuk by adapting HCD. This design was adapted form the Google Material Design Guidelines made by Google. Furthermore, the evaluation to the results of designing the user interface application is needed to determine the level of usability user-acceptability level. The evaluation of the user interface design is done by using System Usability Scale Questionnaaire that contains 10 statements about usability testing. This user interface design got 77,25 of the SUS score, which means that the user interface design of Travelingyuk mobile-based application is well accepted by users.